185k views
4 votes
Helpppppppppppppppppp

Helpppppppppppppppppp-example-1

1 Answer

1 vote

Option D:


\left(y^(2)+3 y+7\right)\left(8 y^(2)+y+1\right)=8 y^(4)+25 y^(3)+60 y^(2)+10y+7

Solution:

Given expression is
\left(y^(2)+3 y+7\right)\left(8 y^(2)+y+1\right).

To find the product of the expression:


\left(y^(2)+3 y+7\right)\left(8 y^(2)+y+1\right)

Multiply each term of the first term with each term of the 2nd term.


=y^(2)\left(8 y^(2)+y+1\right) +3 y\left(8 y^(2)+y+1\right) +7\left(8 y^(2)+y+1\right)

Using the exponent rule:
a^m \cdot a^n = a^(m+n)


=\left(8 y^(4)+y^3+y^2\right) +\left(24 y^(3)+3y^2+3y\right) +\left(56 y^(2)+7y+7\right)


=8 y^(4)+y^3+y^2+24 y^(3)+3y^2+3y+56 y^(2)+7y+7

Arrange the terms with same power.


=8 y^(4)+y^3+24 y^(3)+y^2+3y^2+56 y^(2)+7y+3y+7


=8 y^(4)+25 y^(3)+60 y^(2)+10y+7

Hence option D is the correct answer.


\left(y^(2)+3 y+7\right)\left(8 y^(2)+y+1\right)=8 y^(4)+25 y^(3)+60 y^(2)+10y+7

User Utkonos
by
6.5k points